Guanidinylations of albumin decreased binding capacity of hydrophobic metabolites. (19th May 2015) - Rueth, M.; Lemke, H.‐D.; Preisinger, C.; Krieter, D.; Theelen, W.; Gajjala, P.; Devine, E.; Zidek, W.; Jankowski, J.; Jankowski, V.
Abstract Aim As post‐translational modifications of proteins may have an impact on the pathogenesis of diseases such as atherosclerosis, diabetes mellitus and chronic kidney disease (CKD), post‐translational modifications are currently gaining increasing interest. In this study, a comprehensive method for analysis of these post‐translational modifications is established for the clinical diagnostic routine. Methods Here, we analysed albumin – the most abundant plasma protein in human – isolated from patients with CKD and healthy controls by chromatographic steps and identified by MALDI mass spectrometry. Post‐translational modifications of albumin were identified after digestion by analysing mass signal shifts of albumin peptides using pertinent mass databases. Results Albumin isolated from plasma of patients with CKD but not from healthy control subjects was specifically post‐translationally modified by guanidinylation of lysines at positions 249, 468, 548, 565 and 588. After identification of guanidinylations as post‐translational modifications of albumin isolated from patients with CKD, these modifications were quantified by mass spectrometry demonstrating a significant increase in the corresponding mass signal intensities in patients with CKD compared to healthy controls. The relative amount of guanidinylation of lysine at position 468 in patients with CKD was determined as 63 ± 32% (N = 3). Subsequently, we characterized the pathophysiological impact of the post‐translational guanidinylation on the binding capacity of albumin for representative hydrophobic metabolic waste products. In vitro guanidinylation of albumin from healthy control subjects caused a decreased binding capacity of albumin in a time‐dependent manner. Binding of indoxyl sulphate (protein‐bound fraction) decreased from 82 ± 1% of not post‐translationally modified albumin to 56 ± 1% after in vitro guanidinylation (P < 0.01), whereas the binding of tryptophan decreased from 20 to 4%. These results are in accordance with the binding of indoxyl sulphate to albumin from healthy control subjects and patients with CKD (88 ± 3 vs. 74 ± 10, P < 0.01). Thus, in vitro post‐translational guanidinylation of albumin had a direct effect on the binding capacity of hydrophobic metabolites such as indoxyl sulphate and tryptophan. Conclusion We used a mass spectrometry‐based method for the characterization of post‐translational modification and demonstrated the pathophysiological impact of a representative post‐translational modification of plasma albumin. The data described in this study may help to elucidate the pathophysiological role of protein modifications.